Incidence, predictors, bacterial isolate, antibiotic susceptibility pattern and treatment outcomes among patients who underwent major surgery in public hospitals in Eastern Ethiopia: a prospective multicenter cohort study - Abdela, Jemal; Yusuf, Mohammed; Adem, Fuad; Amin, Abdi; Mohammedsani, Burka; Abdurke, Mohammed; Mehadi, Ame; Abdu, Ahmedmenewer; Mohammed, Hussein (Frontiers in Bacteriology, 2025)
BackgroundPatients who suffer from surgical site infections (SSIs) bear a heavy clinical burden. Longer hospital stays are more likely for patients with SSIs because they are more likely to require treatment in an intensive care unit or to be readmitted to the hospital. Drug-resistant bacterial infections are becoming more common, which is one of the main challenges to effectively treating SSIs in hospitals.ObjectiveThe study aimed to determine the incidence, bacterial isolates, and susceptibility patterns among patients who had undergone major surgical procedures in eastern Ethiopia.MethodsHospital-based prospective multicenter cohort study design was used to determine the incidence of SSIs at public hospitals in eastern Ethiopia. A systematic sampling technique was used to determine the number of patients to participate from each hospital. Data were collected using pre-tested structured questionnaires, standard microbiological operating procedures were used, and the collected wound swab samples were transported to the Hiwot Fana Specialized Comprehensive University Hospital microbiology laboratory unit for identification of bacterial pathogens and antibiotics susceptibility test. The collected data was cleaned, entered and analyzed using SPSS version 22. A P-value <0.05 is considered as statistically significant.ResultsOut of 801 patients who had undergone surgery for different indications, 137(17.1%) (95% CI: 14.6–19.9) of them developed SSIs. Patients with contaminated wound type (AOR: 14.725, 95%CI: 8.210-26.410), who stayed more than 7 days in the hospitals (AOR: 2.45, 95%CI:1.113-5.402), those surgical procedures took more than 60 minutes (AOR:2.598, 95%CI: 1.217-5.546), who did not receive antibiotics prophylaxis (AOR: 5.506, 95%CI: 3.006-10.084), and the presence of comorbidity(AOR: 4.088, 95%CI: 2.266-7.375) were associated with a high risk of developing SSIs. A majority of bacterial isolates from SSIs were gram-negative (66.1%). Of the specific bacterial isolates, S. aureus was the predominant (30.5%) followed by E. coli (18.6%). S. aureus showed a multi-drug resistance against commonly used antimicrobials with some degree of susceptibility to vancomycin. Klebsiella pneumonia and E.coli were multi-drug resistant isolates, but they had a better susceptibility to meropenam, gentamycin, and piperacillin with tazobactam.ConclusionThe presence of contaminated wound type, prolonged hospital stay, longer procedures, absence of antibiotic prophylaxis, and comorbidity increase the incidence of SSIs. S. aureus, Klebsiella pneumonia, and E.coli showed high resistance to multiple antibiotics commonly used in the management of SSIs. Therefore determining their antimicrobial susceptibility and providing defined antimicrobial therapy could lower morbidity, mortality, and healthcare costs, and could improve in-hospital outcomes is recommended to use vancomycin, meropenam, gentamycin, and piperacillin with tazobactam because of the observed susceptibility of common isolates for these drugs in the study area.